Optimization and synergistic enhancement of microalgae productivity in laboratory raceway ponds via co-regulation of automated light-supplemented mixers and electric field system - Siyuan Ren; Cong Shao; Feifei Zhu; Michael Schagerl; Xinjuan Hu; Mostafa Sobhi; Ling Xu; Jingya Qian; Shuhao Huo (Biotechnology for Biofuels and Bioproducts)
Abstract Raceway pond systems face inherent challenges in achieving optimal biomass productivity due to limitations in vertical mixing efficiency and uneven light distribution, compounded by the intrinsic dilute nature of phototrophic cultures. The combination of automated light-supplemented mixers and electric field treatment introduces a promising strategy to enhance raceway pond gas‒liquid mass transfer, improve microalgae biomass production, and increase carbon fixation. Computational fluid dynamics simulations identified an optimal mixing configuration employing a 75° inclined blade rotating counterclockwise at 300 rpm, which reduced dead zones from approximately 15.5% to 1.1% and shortened the light–dark exposure of cells to 2.7 s in a laboratory-scale raceway pond (71.4 dm3). Additionally, daily one-hour electrostatic field stimulation at 0.6 V cm⁻1 during the logarithmic growth phase significantly enhanced algal growth. The novel raceway pond system achieved a 20% increase in the productivity of Limnospira fusiformis and elevated the maximum carbon fixation rate to 0.14 g L⁻1 d⁻1, representing a 43% improvement and the high-value phycocyanin increased by 14.4%. This approach enhanced mixing efficiency and light utilization, providing a scalable strategy for high-value microalgae production in controlled bioreactors. Graphical abstract